(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Huricain Katrina was a natural disaster that had a negative response on the political, economical, sociological and evironmental affects in America. In light of what happened, the levies should be rebuilt to become more secure, land sites should be cleaned up and small shops, restaurants and an historical museum should be made to perserve New Orleans culture. Many contributions should be made to recreate the atmosphere that was lost by Hurricane Katrina by many toursist who would visit this historic site to have a memorable experience of New Orleans culture.